Study on Effect of Pre-sowing Treatments on Germination of Ribes orientale Desf. Seeds - Sharma, San Deep; Kumar, Surinder; Thakur, K. S.; Negi, P. S. (Indian Forester, 2005)
Gooseberry (Ribes orientale Desf.) is an important shrub of higher Himalayan regions and could be a potential species for cold desert areas. A study was conducted to determine the pre-sowing treatment in seeds of this species to overcome dormancy. The ripened berries were collected from Sangla valley in Himachal Pradesh and were immediately depulped and, airdried. Seeds were sown in petridishes in seed germinator after giving various pre-sowing treatments. It was found that the treatment of conc. H2SO4 for 1 minute followed by washing and 24 hours soak in cold water excelled others in germination per cent (58%) and germination energy per cent (51 %). This suggests the existence of seed coat dormancy in the seeds of Ribes orientale. Further the increase of germination per cent in best treatment over control was only 24.5% which suggested that the other factors were also responsible for setting dormancy in the species besides hard seed coat which need deeper investigation.